Closed fractures of the tibial shaft in adults. Issue 2 (April 2017) - Taki, Hussein; Memarzadeh, Arman; Trompeter, Alex; Hull, Peter
Abstract: Diaphyseal tibial fractures are the most common long bone fracture. There are a variety of treatment options, both operative and non-operative, and satisfactory outcomes are reliant on a thorough understanding of the strengths and weaknesses of the different treatment modalities and their appropriate application. Certain fracture patterns present particular difficulties and these must be recognized preoperatively so that a suitable surgical strategy can be executed.